2022
DOI: 10.1002/jbm.a.37362
|View full text |Cite
|
Sign up to set email alerts
|

Sustained released of bioactive mesenchymal stromal cell‐derived extracellular vesicles from 3D‐printed gelatin methacrylate hydrogels

Abstract: Extracellular vesicles (EVs) represent an emerging class of therapeutics with significant potential and broad applicability. However, a general limitation is their rapid clearance after administration. Thus, methods to enable sustained EV release are of great potential value. Here, we demonstrate that EVs from mesenchymal stem/stromal cells (MSCs) can be incorporated into 3D-printed gelatin methacrylate (GelMA) hydrogel bioink, and that the initial burst release of EVs can be reduced by increasing the concentr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 36 publications
(63 reference statements)
1
30
0
Order By: Relevance
“…The section (perpendicular to an axis) of conical microneedle was characterized to further confirm that the GelMA-MN@3D-Exo internal contained 3D-Exo particles through the high-resolution SEM, as shown in Figure E. The release efficiency of 3D-Exo from GelMA-MN@3D-Exo in vitro is an important consideration for application . Thus, GelMA-MN hybrid with 3D-Exo labeling with PKH67 dye was immersed in phosphate buffer solution (PBS) at 37 °C to mimic the release environment in vivo .…”
mentioning
confidence: 95%
“…The section (perpendicular to an axis) of conical microneedle was characterized to further confirm that the GelMA-MN@3D-Exo internal contained 3D-Exo particles through the high-resolution SEM, as shown in Figure E. The release efficiency of 3D-Exo from GelMA-MN@3D-Exo in vitro is an important consideration for application . Thus, GelMA-MN hybrid with 3D-Exo labeling with PKH67 dye was immersed in phosphate buffer solution (PBS) at 37 °C to mimic the release environment in vivo .…”
mentioning
confidence: 95%
“…Contrary to the core bioink solutions, the shell bioink printing parameters, namely the temperature and inlet pressure, were less strict to begin with. EVs were shown to keep their membrane stability even when subjected to relatively high shear stress (>1 bar) [ 65 , 66 ]. Nevertheless, the design of the delivery compartment demanded higher bio-printing resolution to allow fabrication of controlled porosity of the printed pattern, allowing proper mass transfer to the CP interior.…”
Section: Discussionmentioning
confidence: 99%
“…This finding sets the ground for an additional mechanism of sustained release of EVs from polymer-based matrices, mediated by affinity binding. Thus far, EVs sustained delivery was only attempted by encapsulation inside a scaffold or hydrogel, making matrix degradation the limiting factor for drug release rate [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to incorporate EVs into 3D-printable bio-ink. Born et al incorporated MSC-derived EVs into GelMA hydrogel bio-ink and demonstrated that increasing the concentration of a crosslinker during gelation can improve the sustained release of the pro-angiogenic EVs [ 182 ]. Chen et al, used a bio-ink composed of MSC-derived exosomes, decellularized cartilage ECM, and GelMA hydrogel to 3D print a biocompatible scaffold which was implanted on a rabbit model with an osteochondral defect.…”
Section: Hard Porous and Fibrous Scaffoldsmentioning
confidence: 99%